Inclusión educativa en estudiantes de todos ABC campaña de alfabetización, educación básica y bachillerato monseñor Leónidas Proaño en la unidad educativa “pedro Vicente Maldonado - Jesica Estefanía, Sánchez Ramírez (2021)
ABSTRACT The Educational inclusion is an educational model that allows responding to the diversity of the special educational needs of all students through participation in learning, cultures and communities promoting quality education. Given this, the objective has been set to determine the educational inclusion of students with special educational needs associated with a disability in Todos ABC Literacy, Basic Education and High School Campaign “Monsignor Leónidas Proaño”. The present investigation is of a mixed character, with a non-experimental design, of a propositional, transversal and field type; This made it possible to design two instruments, a survey aimed at teaching staff, with parameters that allowed us to investigate inclusive knowledge, attitudes and practices, and an interview aimed at the administrative staff of the institution in order to know the existing levels and types of disability; the data derived from these instruments were tabulated, plotted, analyzed and interpreted; Noting that within the educational institution there are three types of physical, visual and intellectual disability and the low level of knowledge that teachers have regarding what the educational inclusion process implies. Keywords: ABC Campaign, Educational Inclusion, Special Educational Needs. Firmado electrónicamente por: MARITZA DE LOURDES CHAVEZ AGUAGALLO Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324